2009
DOI: 10.1143/jjap.48.07gj09
|View full text |Cite
|
Sign up to set email alerts
|

Simple Analysis of the Pulse Wave for Blood Vessel Evaluation

Abstract: A pulse wave is considered to be a good indicator to evaluate the viscoelastic properties of blood vessels. The wave is composed of an incident wave and a reflected wave. The evaluation of blood vessels may be possible from the analysis of this reflected wave, because the reflected wave propagates to the peripheral artery. We propose a simple method of estimating the reflected wave from the pulse wave observed at common carotid artery, making use of a commercial piezoelectric transducer. First, we estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…This technique will be useful for the medical evaluation of vessel wall elasticity. 17) However, in the analysis, we assumed the blood vessel as an elastic tube and estimated the forward wave from the blood flow velocity waveform. Of course, this assumption should be carefully considered because the actual vessel wall is a viscoelastic material.…”
Section: Introductionmentioning
confidence: 99%
“…This technique will be useful for the medical evaluation of vessel wall elasticity. 17) However, in the analysis, we assumed the blood vessel as an elastic tube and estimated the forward wave from the blood flow velocity waveform. Of course, this assumption should be carefully considered because the actual vessel wall is a viscoelastic material.…”
Section: Introductionmentioning
confidence: 99%
“…1. By assuming the model artery to be an elastic tube, we estimated the pressure wave from the measured flow velocity waveform using a one-dimensional continuity equation and an elastic model [2,3] .…”
Section: Estimation Of Reflected Wavementioning
confidence: 99%
“…Because attenuation of the reflected wave changes markedly due to the arterial stiffness, wave properties of this reflected wave give us information of arterial stiffness. In previous study, we have proposed a simple method to extract the reflected wave from the observed pulse wave [2,3] , and pointed that the amplitudes of the reflected wave increased owing to age. However, the propagation properties of the reflected wave were not perfectly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…change dramatically due to the age. This seems to result from decreasing the force of cardiac contraction with the age and the superposition of the reflected waves with negative amplitude of blood flow [4].…”
Section: B Data Collectionmentioning
confidence: 99%
“…In previous study, we focused on the pulse wave measured on the skin surface as one such technique [4]. The pulse wave is a wave composed of the displacement components due to the forward and backward pressure waves.…”
Section: Introductionmentioning
confidence: 99%